2023
DOI: 10.3892/etm.2023.11970
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the balance of Th17/Treg cells and oxidative stress markers in patients with HIV‑associated pulmonary tuberculosis who develop IRIS

Abstract: Tuberculosis (TB) is the most common opportunistic infection in patients with acquired immunodeficiency syndrome (AIDS) caused by human immunodeficiency virus (HIV) infection and is one of the primary causes of death from AIDS. The increased accessibility to highly active antiretroviral therapy (HAART) has significantly improved the clinical outcome of patients with HIV infection. However, following ART, rapid restoration of the immune system leads to immune reconstitution inflammatory syndrome (IRIS). Oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…There are no concrete answers regarding GSH as a therapy option for the management of IRIS at the moment. However, a 2023 study followed 316 patients in China over 12 weeks of HAART therapy and found increases in malondialdehyde (MDA) and Th17 cell counts and decreases in superoxide dismutase (SOD) and Treg levels [ 71 ]. This constellation of findings indicates that GSH supplementation may be a viable treatment option for patients with IRIS or as a prophylactic agent in patients starting HAART.…”
Section: Glutathione: Treating Hiv- and Aids-related Diseasesmentioning
confidence: 99%
“…There are no concrete answers regarding GSH as a therapy option for the management of IRIS at the moment. However, a 2023 study followed 316 patients in China over 12 weeks of HAART therapy and found increases in malondialdehyde (MDA) and Th17 cell counts and decreases in superoxide dismutase (SOD) and Treg levels [ 71 ]. This constellation of findings indicates that GSH supplementation may be a viable treatment option for patients with IRIS or as a prophylactic agent in patients starting HAART.…”
Section: Glutathione: Treating Hiv- and Aids-related Diseasesmentioning
confidence: 99%
“…In IRIS, the immune response is overly robust and causes injury to the host. Patients with IRIS will have increased malondialdehyde levels, increased Th17 cell counts, decreased superoxide dismutase levels, and decreased Treg cell counts [ 115 ]. Our lab also found that glutathione seems to stabilize Th17 cell counts, evidenced by stabilized IL-17 levels after liposomal glutathione supplementation [ 56 ].…”
Section: Glutathione In Secondary Viral Fungal and Parasitic Brain In...mentioning
confidence: 99%